1990
DOI: 10.1111/j.1528-1157.1990.tb05522.x
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic Drug Treatment of Benign Childhood Epilepsy with Rolandic Spikes: Is It Necessary?

Abstract: Ten untreated and 20 treated patients with benign childhood epilepsy with rolandic (centrotemporal) spikes (BERS) were studied retrospectively after recovery. Seizure frequency, seizure recurrence, and duration of active epilepsy were similar in both groups. No differences were found in social adjustment. Antiepileptic treatment may be unnecessary in most cases of BERS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

1994
1994
2013
2013

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 21 publications
0
41
0
1
Order By: Relevance
“…Unfortunately, data available on the natural course of BCECTS are scarce. Seizures are difficult to control with drugs in 40-50% of cases (Ambrosetto and Tassinari, 1990), and they appeared to be frequent in only 6% of patients (Loiseau et al, 1988). Seizures are difficult to control with drugs in 40-50% of cases (Ambrosetto and Tassinari, 1990), and they appeared to be frequent in only 6% of patients (Loiseau et al, 1988).…”
Section: Treatmentmentioning
confidence: 98%
See 1 more Smart Citation
“…Unfortunately, data available on the natural course of BCECTS are scarce. Seizures are difficult to control with drugs in 40-50% of cases (Ambrosetto and Tassinari, 1990), and they appeared to be frequent in only 6% of patients (Loiseau et al, 1988). Seizures are difficult to control with drugs in 40-50% of cases (Ambrosetto and Tassinari, 1990), and they appeared to be frequent in only 6% of patients (Loiseau et al, 1988).…”
Section: Treatmentmentioning
confidence: 98%
“…Less frequently ictal manifestations include: (1) clonic jerks involving the arm and the leg of one side, with postictal paresis; and (2) generalized seizures which are not infrequently observed in younger children and probably related to rapid generalization of focal seizures. No differences in seizure frequency, seizure relapsing, duration of active period of epilepsy, and social adjustments have been found between BCECTS patients receiving an antiepileptic drug (AED) and those left "untreated" (Ambrosetto and Tassinari, 1990). Several longterm follow-up studies confirmed the good prognosis (Loiseau et al, 1988), and over 90% of the cases are in remission by 12 years of age.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…17 In children, in addition to the recurrence risks, treatment decisions should take account of whether the seizures are part of a benign self-limited syndrome such as benign Rolandic epilepsy as well as seizure frequency and duration. [45][46][47] The authors often do not treat otherwise normal children with infrequent brief seizures even after two or three seizures have occurred. 45,46 Data from randomized clinical trials of children and adults who present with a first unprovoked seizure have shown that AED therapy reduces the risk of seizure recurrence by approximately half.…”
Section: When Is Treatment With Aeds Indicated?mentioning
confidence: 99%
“…5 Problems with ascribing a causative relationship include imprecise definitions of narcolepsy 6 and difficulty ruling out a coincidental occurrence of two unrelated disorders. Eighteen patients were identified, nine with narcolepsy commencing within 1 year before or after the other disorder.…”
Section: Narcolepsy Associated With Other Central Nervous System Disomentioning
confidence: 99%
“…1,2 Partialonset seizures, typically nocturnal, begin between 3 and 13 years of age with remission by 16 years. [5][6][7][8][9] We studied a populationbased cohort with BECT comparing daily treatment with AED versus no medication. 4 Not all children with BECT require antiepileptic drug (AED) treatment.…”
mentioning
confidence: 99%